It is not to Run but to Win: Traditional-Religious Muslim Women’s Agency in Iran and Türkiye - Zainab Mesgartehrani; Abbas Varij Kazemi; Zahra Bakhtiari (İstanbul Üniversitesi Kadın Araştırmaları Dergisi)
Despite widespread assumptions about women’s agency in the Middle East that show the concept of agency as not typically useful to them and submission and obedience as characteristics typically used to describe these women, this study was able to show there is insufficient knowledge about the meanings of women’s agency for women living in conservative non-western regions, especially the Middle East. We gathered data from 50 lower-middle-class traditional-religious Muslim women in Ankaras and Tehran. We used a qualitative method, thematic analysis, and cognitive and semi-structured interviews. By emphasizing the quiet encroachment theory, the result shows that the encroachment of religious women in their everyday lives may be silent, hidden, and slow. Still, these women have been able to demonstrate their agency despite low education and economy. They don't act and think according to the traditional patterns of religiosity or social, cultural, and religious expectations. They create environments and resources for their freedom of action and fulfill their wishes outside. Women make decisions as active agents in the decision-making process after exiting their safe space and experiencing the joys of change.